From Creep Damage Mechanics to Homogenization Methods A Liber Amicorum to celebrate the birthday of Nobutada Ohno - Altenbach, Holm.; Altenbach, Holm.; Matsuda, Tetsuya.; Matsuda, Tetsuya.; Okumura, Dai.; Okumura, Dai. (Advanced Structured Materials,, 2015)
This volume presents a collection of contributions on materials modeling, which were written to celebrate the 65th birthday of Prof. Nobutada Ohno. The book follows Prof. Ohno’s scientific topics, starting with creep damage problems and ending with homogenization methods.